Pengaruh variasi kuat arus dan kecepatan pengelasan terhadap sifat mekanik hasil pengelasan SAW plat baja SS41 grade A - IN Budiarsa; IGN Nitya Santhiarsa (Jurnal Energi Dan Manufaktur, 2006)
Welding is a method used to joint metal or metal alloy that take heat energy from welding machine. On welding process, there is occurred the fusion between base metal with filled metal. In base metal, there is founded heat affected zone(HAZ) which to go throw heating and cooling cycles that produce the changes of microstructure of metal so that make mechanical behavior of material changes. This research discuss the affect of variation of electric current and welding speed on mechanical behavior of steel plate SS41 Grade A, that is for understanding the changes of toughness caused by welding process, so then could choice the right parameter welding and know the changes of material toughness. The method that used in this research is factorial experiment with two factor are electric current and welding speed. Based on research results, both of electric current and welding speed have real impact for toughness, where electric current more and more high make toughness decrease, afterward, welding speed more and more high make toughness increase.